2015
DOI: 10.1016/j.chemosphere.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Modelling metal accumulation using humic acid as a surrogate for plant roots

Abstract: . 2015. Modelling metal accumulation using humic acid as a surrogate for plant roots.Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Antunes et al similarly showed that the onset of acute toxicological response of barley to Cu was better correlated to the low-affinity ligands subsequent to the saturation of high-affinity sites. In plants, the large number of low-affinity sites would be the carboxylic acids, which reversibly bind a number of metals without the same degree of differentiation among metals as would be expected for high-affinity sites. , Although the development of an mBLM with different biotic ligands for Cu and Zn might improve model fits, such a model construct would require even more model parameters. In addition, it should be noted that the BLM requires a large data set to fit all model parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antunes et al similarly showed that the onset of acute toxicological response of barley to Cu was better correlated to the low-affinity ligands subsequent to the saturation of high-affinity sites. In plants, the large number of low-affinity sites would be the carboxylic acids, which reversibly bind a number of metals without the same degree of differentiation among metals as would be expected for high-affinity sites. , Although the development of an mBLM with different biotic ligands for Cu and Zn might improve model fits, such a model construct would require even more model parameters. In addition, it should be noted that the BLM requires a large data set to fit all model parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The model assumes that mixture exposure, and hence toxicity, depends on the interactions of metals and protons with the organism at reversible binding sites, and that these competitive chemical reactions can be represented by competitive binding to particulate humic acid. , The particulate humic acid (HA)-phase database of WHAM VII can be easily used to calculate the concentrations of metals on HA, which is a proxy for metabolically available metal . The ability of WHAM to model metal accumulation using humic acid as a surrogate for effects on several species has been reported in several studies. , The WHAM- F tox model was initially developed to quantify the joint toxicity of metals and protons to aquatic organisms. Its applicability to predict mixture toxicity to plants exposed in different soils has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the developed model was evaluated by comparing the analysed metal concentration in the uninfected chub, the infected chub, and the acanthocephalans with the corresponding predicted concentration according to the developed model by using different means of statistical parameters. The capacity of the model in explaining the variations in the metal concentration in the chub or in the acanthocephalans was expressed by the value of r 2 and p [81]. In addition, the deviation between the measured and the predicted concentrations was represented by the values of mean absolute error (MAE) and root mean square error (RMSE) [81].…”
Section: Methodsmentioning
confidence: 99%
“…The capacity of the model in explaining the variations in the metal concentration in the chub or in the acanthocephalans was expressed by the value of r 2 and p [81]. In addition, the deviation between the measured and the predicted concentrations was represented by the values of mean absolute error (MAE) and root mean square error (RMSE) [81]. The validation for Fe, Cu, and Zn at the background concentrations of the tap water was carried out assuming that at those low concentrations, the accumulation of the metals in the chub was not affected by the acanthocephalans.…”
Section: Methodsmentioning
confidence: 99%
“…Az anaerob fermentáció optimális működéséhez a mikrobiális összetétel alapján nyomelem adagolás szükséges (ZHANG-JAHNG 2012, QIANG et al 2013. A metántermelésre gyakorolt pozitív hatások mellett azonban a nehézfémek akkumulációja kedvezőtlen folyamatokat indíthat el a talaj ökoszisztémában (WALTER et al 2006, SALAZAR et al 2012, amely további negatív hatásként jelentkezhet az élelmiszerláncban (WAHSHA et al 2014, LE et al 2015. A lehetséges következmények azonosítása érdekében ökotoxikológiai tesztek elvégzése indokolt.…”
Section: Bevezetésunclassified